Decarbonising urban transport: an overview of electric vehicles, public transport, and sustainable infrastructure in achieving net-zero emissions - Emmanuel Ndhlovu; David Mhlanga; Barbra Duri (Discover Global Society, 2025)
Abstract Traditionally, the transport sector contributes significantly to global greenhouse gas (GHG) emissions. Transitioning from gasoline-powered to electric vehicles is the most practical way to decarbonise the sector. This article contributes to ongoing debates about environmental sustainability by focusing on how the transport sector can contribute to sustainability. This article explores how the adoption of Electric and battery-powered vehicles can help reduce GHG emissions. It identifies the benefits of these in decarbonisation and examines the potential challenges to EV adoption. The article is based on a review of primary and secondary literature in both grey and academic formats, including government reports, reports of policy and research institutions, newspaper articles and blogs and academic texts, including books, book chapters, and journal articles. The review shows that Electric and battery-powered vehicles hold significant potential to decarbonise the transport sector. There are, however, significant challenges to the sector's decarbonisation, including affordability, accessibility, infrastructural, and consumer attitudinal challenges. Policy interventions should include the provision of incentives, expanding innovation and research, expanding infrastructure in urban areas to boost public transport, promoting data transparency and availability of net-zero emission products and facilitating investment, knowledge sharing and capacity building.